The Hill We Climb: The Future of Women of Color Leadership Development. Issue 3 (August 2022) - Carter, Angela D.; Sisco, Stephanie
The Problem: There has been sparse research on the intersectional nature of the leadership practices of women of color since the last special issue in Advances in Developing Human Resources (ADHR). Included here are insights and recommendations for HRD practitioners and scholars on developing women leaders of color. The Solution: In this concluding article, we make recommendations for future theory and practice centered on leadership for women of color using Amanda Gorman's 2021 inaugural poem as a backdrop. Stakeholders: In order to encourage further thought and action for researchers and practitioners in Human Resource development (HRD), this article is intended to provoke thought on women leaders of color and provide impetus toward future HRD scholarship.